Correlation between plasma lipid levels in patients with different oral pre-cancerous lesions - Goyal, Sakshi; Srivastava, Saurabh; Jafar, Tabrez; Ullah, Sami; Bhat, Priyanka; Alam, Imran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Oral precancerous lesions could be defined as the lesions present in oral cavity that have a potential to become cancer. Recognition of precancerous lesions has its own significance as it helps in early detection of risk of cancer which in itself is quite useful for formulating appropriate preventive strategies that could assure better survival rates. The aim of the study was to assess the correlation of lipid levels in patients with different oral precancerous lesions. Methods: A total of 150 patients with oral lesions attending the department of otorhinolaryngology at Era’s Lucknow Medical college and Hospital, Lucknow, were included in the study. A biopsy specimen was taken from each patient along with 5 ml fasting blood sample for serum lipid estimation which was done by dry chemistry Chemino Heinz method. Results: A total of 150 patients with age ranging from 13-70 years and a male is to female ratio of 1.68 was studied. Burning sensation was the most common symptom and OSMF being the most common diagnosis. All the components of lipid profile except HDL of patients with different histopathological diagnosis were found to be comparable. No association of derangement in any of the components of lipid levels and histopathological diagnosis was observed. Conclusions: The findings of present study showed that lipid levels in patients with precancerous oral lesions are generally of lower order. However, the present study could not assess a significant association between lipid levels and different types of oral premalignant lesions.